Răspuns :
Aplicam formula:
[tex]1+2+3+..+n = \frac{n*(n+1)}{2} [/tex]
=>
[tex](1+2+3+....+2012)*( \frac{1 }{2012} - \frac{1 }{2012*2013} ) = \\ \\ = \frac{2012*2013}{2}*( \frac{1 }{2012} - \frac{1 }{2012*2013} )= \\ \\ \frac{2012*2013}{2*2012}-\frac{2012*2013}{2*2012*2013}= \frac{2013}{2}- \frac{1}{2}= \frac{2012}{2}= 1006 [/tex]
[tex]1+2+3+..+n = \frac{n*(n+1)}{2} [/tex]
=>
[tex](1+2+3+....+2012)*( \frac{1 }{2012} - \frac{1 }{2012*2013} ) = \\ \\ = \frac{2012*2013}{2}*( \frac{1 }{2012} - \frac{1 }{2012*2013} )= \\ \\ \frac{2012*2013}{2*2012}-\frac{2012*2013}{2*2012*2013}= \frac{2013}{2}- \frac{1}{2}= \frac{2012}{2}= 1006 [/tex]